2017
DOI: 10.1186/s13011-017-0110-9
|View full text |Cite
|
Sign up to set email alerts
|

Men’s and women’s response to treatment and perceptions of outcomes in a randomized controlled trial of injectable opioid assisted treatment for severe opioid use disorder

Abstract: BackgroundTo test whether there are gender differences in treatment outcomes among patients receiving injectable opioids for the treatment of long-term opioid-dependence. The study additionally explores whether men and women have different perceptions of treatment effectiveness.MethodsThis study is a secondary analysis from SALOME, a double-blind, phase III, randomized controlled trial testing the non-inferiorirty of injectable hydromorphone to injectable diacetylmorphine among 202 long-term street opioid inje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 48 publications
0
25
0
Order By: Relevance
“…Indeed, studies on heroin assisted treatment in both Canada and Europe have found that diacetylmorphine is more effective than oral methadone for reducing illicit opioid use for many individuals [ 31 , 49 , 51 , 52 ], indicating the need to expand opioid substitution models. Further, our study builds on research demonstrating a reduction in illegal activities (e.g., property crime, illegal means of income generation) among people receiving injectable opioid-assisted treatment [ 53 55 ]. This is especially important considering the association between socio-environmental factors, such as poverty, lack of adequate housing, and overdose risk [ 56 59 ], and underscores the potential role of safer supply interventions to address issues at the intersection of drug use and structural vulnerability.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, studies on heroin assisted treatment in both Canada and Europe have found that diacetylmorphine is more effective than oral methadone for reducing illicit opioid use for many individuals [ 31 , 49 , 51 , 52 ], indicating the need to expand opioid substitution models. Further, our study builds on research demonstrating a reduction in illegal activities (e.g., property crime, illegal means of income generation) among people receiving injectable opioid-assisted treatment [ 53 55 ]. This is especially important considering the association between socio-environmental factors, such as poverty, lack of adequate housing, and overdose risk [ 56 59 ], and underscores the potential role of safer supply interventions to address issues at the intersection of drug use and structural vulnerability.…”
Section: Discussionmentioning
confidence: 99%
“…There was little evidence of differences between the supervised injectable heroin and supervised injectable hydromorphone groups across all other secondary outcome comparisons (Oviedo-Joekes et al, 2016). Subgroup analyses by gender or by self-identified Indigenous status showed no significant differences in treatment efficacy across primary or secondary outcomes (Oviedo-Joekes et al, 2017b;Palis et al, 2017).…”
Section: Findings From a More Recently Implemented Rctmentioning
confidence: 91%
“…Our literature search identified five additional articles evaluating the individual-level impacts of HAT based on the Study to Assess Longer-term Opioid Medication Effectiveness (SALOME) (Nikoo et al, 2018;Oviedo-Joekes et al, 2017a;Oviedo-Joekes et al, 2016;Oviedo-Joekes et al, 2017b;Palis et al, 2017), a more recent HAT RCT which did not have published results until after the most recent systematic review.…”
Section: Findings From a More Recently Implemented Rctmentioning
confidence: 99%
“…6 The effectiveness of this program is supported by the rigorous scientific evaluation coming out of the Study to Assess Longerterm Opioid Medication Effectiveness (SALOME) trial, as well as several other heroin-assisted therapy trials. 7 However, the program has limitations with respect to scale-up, owing to the high cost of injectable hydromorphone, the infrastructure requirements and that participants must attend a medical clinic up to three times per day. In an effort to expand access to injectable opioid agonist therapy, a guideline has been developed to support new models for distribution that aim to lower both the barriers to qualify and the requirements to participate.…”
Section: Vulnerable Populationsmentioning
confidence: 99%